Connective financing Chinese infrastructure projects and the diffusion of economic activity in developing countries - Bluhm, Richard; Dreher, Axel; Fuchs, Andreas; Parks, Bradley; Strange, Austin M.; Tierney, Michael J. (CESifo working papers, 2020)
This paper studies the causal effect of transport infrastructure on the spatial concentration of economic activity. Leveraging a new global dataset of geo-located Chinese government-financed projects over the period from 2000 to 2014 together with measures of spatial inequality based on remotely-sensed data, we analyse the effects of transport projects on the spatial distribution of economic activity within and between regions in a large number of developing countries. We find that Chinese-financed transportation projects reduce spatial concentration within but not between regions. In line with land use theory, we document a range of results which are consistent with a relocation of activity from city centers to their immediate periphery. Transport projects decentralize activity particularly strongly in regions that are more urbanized, located closer to the coast, and less developed.